Amphetamine–Dextroamphetamine and Pregnancy: Neonatal Outcomes After Prenatal Prescription Mixed Amphetamine Exposure. Issue 9 (July 2021) - Rose, Sherrill J.; Hathcock, Matthew A.; White, Wendy M.; Borowski, Kristi; Rivera-Chiauzzi, Enid Y.
Objective: A retrospective cohort study was performed to evaluate whether birthweight was less among infants of women taking amphetamine–dextroamphetamine during pregnancy at our academic institution.Method: We identified mother–infant pairs with documented exposure to amphetamine–dextroamphetamine in pregnancy from 2005 through 2015. Patients were matched 2:1 with unexposed controls. Charts were reviewed for known causes of intrauterine growth restriction. Analysis of birthweight used generalized estimating equation blocking on matching. Medical histories were analyzed with χ 2 test or Fisher's exact test.Results: We identified 53 exposed mother–infant pairs. The difference in mean birthweight of infants exposed to amphetamine–dextroamphetamine versus those not exposed was 26.9 g, which is not significant (95% confidence interval [CI] = [−141, 195 g]; p = .75). A significant difference was noted for exposed versus unexposed mothers for comorbid psychiatric illness and history of substance abuse ( p < .001).Conclusion: With a limited sample size, our study suggests no significant difference in birthweight.